The Growth and Performance of the Belarusian Agro-food Industry in 2004-2012 - Shpak, Alexander; Pilipuk, Andrei (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2014)
This paper provides an analysis of agro-food industry growth in Belarus, which is one of the key industries in the economy. Such an analysis allowed us to understand the main forces of relatively successful development. We pointed out that state owned companies in the Belarusian agro-food industry operate as de facto strongly integrated corporate groups which ensures reliable supply of raw materials. In addition, we looked at the government directed lending programs which, through allocation of credit, push funds toward priority subsectors.